THE IMPORTANCE OF SELECTING AND DESIGNING TEACHING MATERIALS FOR ESP CLASSES - Akramova Yulduz Farkhadovna (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract. The purpose of this article is to analyze the important aspects of the selection and design of ESP materials and to show that the success of ESP lessons is closely related to the teacher's ability to choose materials that perfectly match the needs and goals of the students. The paper provides a close analysis of the criteria that ESP teachers should consider when choosing teaching materials. This emphasizes the necessity of choosing them entirely according to students' needs, abilities and preferences.